22@ and the Innovation District in Barcelona and Montreal: A Process of Clustering Development between Urban Regeneration and Economic Competitiveness. (18th December 2011) - Battaglia, Angelo; Tremblay, Diane-Gabrielle
Abstract : This paper analyzes the governance strategy of the 22@ District in Barcelona in order to assess the factors that explain its success and could support the economic reconversion of Montreal's future Innovation District (ID), as well as that of other cities. We examine the case of the 22@ District as a former industrial neighbourhood seen as a "model" of urban regeneration and economic revitalization. Our assumption is that the world's major cities are going through a phase based on the reorganization of central urban areas. Our article evaluates the main factors of urban regeneration in the 22@—district of innovation and it identifies elements of best practices in terms of governance which can be constructive for the "Quartier de l'Innovation" in Montreal and similar projects of other cities. The paper highlights the role of decision makers concerning the process of governance of 22@ and its historic changes, and insists on the the role of socioeconomic actors and territorial factors that could support the level of integration and implementation of Montreal@ID. Our paper highlights the importance of the integration process based on socio-territorial innovations characterizing the Catalan context of 22@ as well as the Innovation District, something useful for other similar initiatives.